Development of a serological assay for Chikungunya virus / Nishakanthi a/p Gopalan - Gopalan, Nishakanthi (2008)
Chikungunya virus (CHIKV) is a RNA virus that belongs to the Alphavirus genus of the family Togaviridae. It is transmitted by Aedes albopictus and Aedes aegypti, and causes clinical symptoms like fever with acute fever, skin rash and athralgia which mimics dengue fever. With current outbreaks of CHIKV in Malaysia, it is essential to develop a serological assay as a tool for laboratory diagnosis and seroprevalence study. An IgG indirect ELISA was developed and used to validate nine samples collected from Bagan Panchor residents one year after an outbreak occurred in 2006. A variety of factors like varying cell culture types (C6/36 and Vero) to prepare the virus lysate antigen, different serum dilutions and the cut-off value determination methods were studied to optimize an IgG indirect ELISA assay. Neutralization assay was used as the gold standard. The IgG indirect ELISA using CHIKV-infected Vero cell lysate antigen performed better compared to CHIKV-infected C6/36 cell lysate antigen. The developed assay had a sensitivity of 100%, poor specificity of 25%, positive predictive value of 62.5%, negative predictive value of 100%, and concordance of 66.7%, compared to neutralization. The poor specificity and non-specific background readings are likely due to the crude total cell lysate used in the assay. Western blot identified the capsid protein as the immunogenic protein, which maybe used as a CHIKV recombinant antigen for further development of a more specific ELISA assay.